2019
DOI: 10.1097/md.0000000000014602
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of p16 protein in nasopharynx cancer patients

Abstract: Background:p16 protein is significantly down-regulated in several cancers, which reveals that it may be a potential biomarker for cancers. However, the clinicopathological and prognostic value of p16 protein in nasopharynx cancer patients remains unclear. Therefore, we performed a meta-analysis to assess the relationships of p16 protein expression with the clinicopathological features and prognosis of nasopharynx cancer.Methods:PubMed, Web of Science, Embase, and Chinese CNKI were searched to obtain eligible d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
(29 reference statements)
0
8
0
1
Order By: Relevance
“…Wang et al concluded that p16-positive patients had superior survival rates compared to p16-negative patients [ 15 ]. A meta-analysis including these three studies, however, failed to show any significant difference in clinical outcomes (OS, PFS) based on p16 positivity [ 11 ]. However, it did demonstrate higher distant metastasis, lymph node metastasis, and TNM staging in patients with down-regulated p16 expression [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al concluded that p16-positive patients had superior survival rates compared to p16-negative patients [ 15 ]. A meta-analysis including these three studies, however, failed to show any significant difference in clinical outcomes (OS, PFS) based on p16 positivity [ 11 ]. However, it did demonstrate higher distant metastasis, lymph node metastasis, and TNM staging in patients with down-regulated p16 expression [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including these three studies, however, failed to show any significant difference in clinical outcomes (OS, PFS) based on p16 positivity [ 11 ]. However, it did demonstrate higher distant metastasis, lymph node metastasis, and TNM staging in patients with down-regulated p16 expression [ 11 ]. Rosalez-Perez et al also described an aggressive clinical course in p16-negative patients who had metastases present at diagnosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasopharyngeal carcinoma (NPC) is an unfrequented tumor with high ratio of death [1][2][3]. The incidence of NPC is relatively low and presents a distinct racial and geographic distribution [4,5].…”
mentioning
confidence: 99%